MODERATING EFFECTS OF RISK MANAGEMENT FUNCTION ON DETERMINANTS OF ENTERPRISE RISK MANAGEMENT IMPLEMENTATION IN MALAYSIAN OIL AND GAS SECTOR: A CONCEPTUAL FRAMEWORK - R, Tasmin; H. M., Muazu (Journal of Technology Management and Business, 2017)
Abstract Enterprise Risk Management (ERM) has been recently acknowledged as one way out of economic crises the world is experiencing. As it has accounted for some business success stories after the 2008 global financial crises. Despite all the good experience, oil and gas sectors of the global economy are still suffering from emerging risk incidences such as dwindling oil prices, pipeline explosions, refinery shut down, staff trips and falls and new regulations. Malaysian oil and gas sector is not an exception, as it has faced and still facing some of these risky turbulances. Previous studies conducted on ERM in Malaysia were mostly on financial institutions, manufacturing sector, measuring performance and firm’s value analysis. It is against this backdrop, in which this paper develops a conceptual framework for a study to be conducted in the future. The research gap is by taking a departure from all those saturated areas to the petroleum industry with concern to ERM implementation intensity, particularly the oil and gas sector in Malaysia. The postulated determinant variables to be examined in the study are firm characteristics, information technology, staff capacity and regulatory framework, using risk management function as a moderating variable, involving major oil and gas industry players, namely Petronas and Hess Corporation. Research significance and the scope of the study were also explained in the paper. Keywords: Implementation, Drivers, Enterprise-Risk-Management, Risk, and Oil-and-Gas